A target-controlled infusion system with bispectral index monitoring of propofol sedation during endoscopic submucosal dissection - Imagawa, Atsushi; Hata, Hidenori; Nakatsu, Morihito; Matsumi, Akihiro; Ueta, Eijiro; Suto, Kozue; Terasawa, Hiroyuki; Sakae, Hiroyuki; Takeuchi, Keiko; Fujihara, Manabu; Endo, Hitomi; Yasuhara, Hisae; Ishihara, Shinichi; Kanzaki, Hiromitsu; Jinno, Hideki; Kamada, Hidenori; Kaji, Eisuke; Moriya, Akio; Ando, Masaharu (Endoscopy International Open, 2015)
Background and study aims: Propofol administration via a target-controlled infusion system with bispectral index monitoring (BIS/TCI system) is expected to prevent complications from sedation during complex and long endoscopic procedures. We evaluated the feasibility of setting the BIS/TCI system for non-anesthesiologist administration of propofol (NAAP) during endoscopic submucosal dissection (ESD).Patients and methods: From May 2009 to February 2013, 250 patients with esophagogastric neoplasms were treated with ESD using the BIS/TCI system with NAAP. In the TCI system, the initial target blood concentration of propofol was set at 1.2 μg/mL. The titration speed of propofol was adjusted according to the BIS score and the movement of the patient. The BIS target level ranged from moderate to deep sedation, at which a stable BIS score between 60 and 80 was obtained.Results: In 80.4 % of patients, it was possible to maintain stable sedation with a blood concentration of propofol of less than 1.6 µg/mL using TCI throughout the ESD procedure. The default setting for ideal blood concentration of propofol was 1.2 μg/mL, because the medians of the lower and upper bounds of blood concentration were 1.2 μg/mL (range 0.6 – 1.8 μg/mL) and 1.4 μg/mL (range 1.0 – 3.8 μg/mL), respectively. Although hypotension occurred in 27 patients (10.8 %), oxygen desaturation occurred in only nine patients (3.6 %), and severe desaturation in only two patients (0.8 %).Conclusions: Using our settings, it is possible for a non-anesthesiologist to maintain stable sedation during a lengthy endoscopic procedure through propofol sedation with a BIS/TCI system.